2004
DOI: 10.1182/blood.v104.11.2397.2397
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Decreases the Thrombotic Complications (DVT) of Liposomal Doxorubicin, Vincristine, Decreased Frequency Dexamethasone and Thalidomide (DVd-T) Treatment of Multiple Myeloma (MM).

Abstract: Patients with plasma cell dyscrasia are at risk to develop DVT (prevalence in MGUS was 8%, in MM 10%) (Cancer101(3):558–566, 2004). The risk has been reported to be higher in newly diagnosed (ND) patients treated with Thalidomide and anthracyclines (Clinical Lymphoma. 4(1):32–5, 2003). DVd-T is effective in the treatment of MM patients but carries an increased risk of DVT. Our incidence of DVT with Thalidomide and Thalidomide/Dexamethasone with slow dose escalation and less frequent Dexamethasone was not diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2005
2005
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…It is uncertain which of these measures accounts for the low incidence of DVT observed. It is worth noting however that the use of aspirin given at the same dose (81 mg/d) was also found in preliminary data to decrease the incidence of DVT during initial therapy with DVd-T (Baz et al, 2004).…”
Section: Discussionmentioning
confidence: 75%
“…It is uncertain which of these measures accounts for the low incidence of DVT observed. It is worth noting however that the use of aspirin given at the same dose (81 mg/d) was also found in preliminary data to decrease the incidence of DVT during initial therapy with DVd-T (Baz et al, 2004).…”
Section: Discussionmentioning
confidence: 75%
“…Treatment should be continued to maximum response plus 3 months. Randomised trials have shown no advantage of continuing chemotherapy beyond this time (Medical Research Council's Working Party on Leukaemia in Adults, 1980;Belch et al, 1988). This applies to patients with stable disease (see Table VIII) as well as those meeting the criteria for response.…”
Section: Initial Chemotherapy Where Hdt Is Not Planned -'Conventionalmentioning
confidence: 99%
“…With the exception of data relating to a-IFN, there remains a lack of data relating to maintenance therapy. Continuing conventional chemotherapy therapy is not beneficial following the achievement of plateau phase (Medical Research Council's Working Party on Leukaemia in Adults, 1980;Belch et al, 1988). Several agents have been studied in maintenance including a-IFN, steroids and newer agents, such as thalidomide, thalidomide analogues and bortezomib.…”
Section: Maintenance Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hassoun et al 27 relataram que, em 31 pacientes fazendo tratamento seqüencial com doxorrubicina e dexametasona, por três meses, e dexametasona e talidomida, por dois meses, e ácido acetil salicílico (81 mg/dia), a incidência de trombose venosa profunda foi de 9,6%. Por sua vez, Baz et al 28 trataram 103 pacientes com mieloma recém-diagnosticado ou em recaída/refratariedade, com o protocolo DVd-T (doxorrubicina peguilada, vincristina, dexametasona com freqüência reduzida e talidomida). Desse total de pacientes, 84 fizeram uso do ácido acetil salicílico, 81 mg por dia.…”
Section: Profilaxia Antitrombótica Com áCido Acetil Salicílicounclassified